The Influence Of Mathematical Anxiety And Logical-Mathematic Intelligence On Students' Learning Outcomes Through Critical Thinking Ability - Arofah, Irvana; Ningsi, Besse Arnawisuda; Sessu, Andi (International Education Trend Issues, 2024)
The research aims to determine the direct and indirect influence of mathematical anxiety, logical-mathematical intelligence, and critical thinking abilities on the learning outcomes acquired by students. Many things affect the teaching and learning process, both from outside the student's environment and from within the student himself. The unpreparedness of external and internal factors will create obstacles in the learning process of the student, which will then affect their learning outcomes. These include mathematical anxiety, mathematical logical intelligence, and critical thinking abilities. Students who experience mathematical anxiety tend to avoid conditions where they feel threatened and stressed. Of course, these people will think or assume negative thoughts about themselves. Mathematical logical intelligence plays a significant role for students in understanding abstract mathematics lessons. The challenge in the world of education is that it requires students to think at higher levels (HOTs). Critical thinking is a logical and natural thinking process that already exists in a person when facing changes in all sectors of life. The method used in this research is structural equation modeling (SEM), which will look at direct and indirect effects. The research results show that 1) mathematics anxiety has a significant positive influence on critical thinking abilities; 2) logical-mathematical intelligence has a significant positive influence on critical thinking abilities; 3) critical thinking skills have a significant positive influence on student learning outcomes; 4) mathematics anxiety has a significant positive influence on student learning outcomes; 5) logical-mathematical intelligence has a significant positive influence on student learning outcomes; 6) mathematics anxiety has a significant positive influence on student learning outcomes through critical thinking skills; and 7) logical-mathematical intelligence has an insignificant positive influence on student learning outcomes through critical thinking skills.